Peningkatan Kemampuan Motorik Kasar Anak Usia Dini dalam Lingkungan Sekolah RA Sabilal Muhtadin - Bagus Tri Gryatama; Fatimah Azzahra (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This article discusses efforts to improve gross motor skills in young children in the RA SABILAL MUHTADIN school environment. This research focuses on the implementation of a special program designed to stimulate gross motor development through structured play activities. Research methods include observation, intervention, and evaluation of children's progress over a certain period of time. The results show that this approach was successful in significantly improving children's gross motor skills, making a positive contribution to their physical development in a formal education environment.